Degradation study of organic light-emitting diodes with solution-processed small molecule phosphorescent emitting layers. Issue 37 (1st September 2016) - Liu, Shuyi; Peng, Cheng; Cruz, Alexandria; Chen, Ying; So, Franky
Abstract : Charge injection and solvent impurities effects on degradation of solution-processed small molecule phosphorescent organic light-emitting diodes. Abstract : The degradation mechanisms of solution processed small molecule phosphorescent OLEDs are investigated along with thermal evaporated devices. Hole-induced degradation in the presence of excited states is found to be a major culprit for the fast degradation in solution-processed devices. Degradation in the solution-processed emitting layer (EML) is found to be strongly dependent on the initial hole injection/transport properties of the EML. Gas chromatography-mass spectrometry (GC-MS) studies on solvents used to prepare the solution-processed EMLs reveal that solvent impurities are the dominant reason for their substantially shorter operational lifetime compared with thermal evaporated devices.